Challenges and Factors Associated with Adherence to Non-Pharmaceutical Interventions to Prevent the Spread of COVID-19 in a Slum Setting - Ozichu Ekama Sabdat; Abike Gbajabiamila Titilola; Olurotimi Salako Abideen; Ayoola Oladele David; Odubela Oluwatosin.O.; Nkiru David Agatha; Chukwujekwu Ezechi Oliver; Lawal Salako Babatunde (Journal of Public Health International, 2022)
Objectives This study aims to evaluate the challenges of implementing non-pharmaceutical interventions, assess adherence, accessibility to prevention materials and identify requirements for the control of the spread of COVID-19 among individuals living in a slum-setting in Lagos, Nigeria. Methods This is a five-month cross-sectional study conducted in Makoko, Lagos an urban-slum community. Data on sociodemographic characteristics, living conditions and adherence to COVID-19 prevention strategies were obtained with a semi-structured questionnaire. Logistics-regression model was used to determine factors associated with adherence to COVID-19 preventive measures. Results There was a total of 357 participants who had a mean age of 45.8 ± 12.9 years. Majority were males (62.2%), married (83.8%), self-employed (66.4%), and had secondary education (31.4%). Most participants (93.8%) had no space for self-isolation as majority lived in a one-room apartment (72.8%), shared toilets/kitchen space (64.4 %), had no constant source of water supply (61.9%) and buy water (62.5%). About 98.8% are aware of the COVID-19 pandemic but only 33.9% adhered. Most of the participants disclosed inability to purchase face masks/ hand sanitizers (68.9%). After adjusting for covariates, the ability to afford facemasks/hand sanitizers (P < 0.0001, aOR 6.646; 95% CI: 3.805-11.609), living alone (P < 0.0001, aOR 3.658; 95% CI: 1.267-10.558), and ability to buy water (aOR: 0.27; 95% CI: 0.14-0.50), had greater odds of association with adherence to the non-pharmaceutical COVID-19 preventive measures. Conclusion The lack of isolation space among majority of the respondents calls for concern. Inability to purchase prevention materials is a major factor influencing poor compliance to COVID-19 prevention strategies.
Keywords: COVID-19 prevention